Material-Relational Following of an Artist-Curator Relationship in Movement: A Reflection of my Relationship with the Artist Regitze Karlsen - Friis, Joachim (Art/Research International, 2024)
In this article, I explore insights gained in the investigation of a personal artist-curator relationship using Katve-Kaisa Kontturi’s methodology of material-relational following. In my role as a curator, I track my relationship with Danish artist Regitze Karlsen as it unfolded from 2017 until 2023; from my first meeting with the artist and her work, through collaborative work on an exhibition, and a studio visit afterwards. I show how the method of following provides in-movement knowledge of the artist-curator relation, which makes it possible to conceive of the art-work as an expanded process of ideas, sites, materials, and affects between artworkers. Moving between sections of lived experiences and theoretical reflections, I conclude that the curatorial modes of being hooked, curiosity, and concern, were essential for my following of Regitze’s and my artist-curator relation.